1987
DOI: 10.1161/01.hyp.10.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effects of calcium entry blockers on renal function in hypertension.

Abstract: SUMMARY Characterization of the renal effects of calcium entry blockers has not been easy because the inhibition of Ca 2+ cellular influx alters several regulatory functions. The ability of calcium blockers to dilate renal vasculature and to increase glomerular filtration rate is largely determined by the preexisting vascular tone. However, the increments in sodium excretion could occur without alterations in renal hemodynamics. Calcium blockers could increase sodium excretion by inducing a redistribution of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
1
1

Year Published

1988
1988
1995
1995

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(24 citation statements)
references
References 80 publications
3
19
1
1
Order By: Relevance
“…" 29 This response is what would be expected if the primary effect of verapamil were reduction in preglomerular vascular resistance. If filtration rate were measured in patients shortly after the start of verapamil treatment, an increase in GFR might be observed if the acute hypotensive effects of the calcium entry blocker were prevented; in several studies in patients, increases in GFR have been reported soon after the start of treatment with the calcium entry blocker.…”
mentioning
confidence: 71%
“…" 29 This response is what would be expected if the primary effect of verapamil were reduction in preglomerular vascular resistance. If filtration rate were measured in patients shortly after the start of verapamil treatment, an increase in GFR might be observed if the acute hypotensive effects of the calcium entry blocker were prevented; in several studies in patients, increases in GFR have been reported soon after the start of treatment with the calcium entry blocker.…”
mentioning
confidence: 71%
“…8 They have also been shown to reduce the extent of aortic atherosclerosis in cholesterol-fed rabbits. 9 Within the kidney, calcium channel blockers can vasodilate afferent arterioles 10 and might increase the glomerular ultrafiltration coefficient, which is determined in part by mesangial cell function. In patients with hypertension and renal insufficiency, short-term treatment with calcium channel blockers has been shown to improve glomerular filtration rate.…”
Section: Camentioning
confidence: 99%
“…8 - 10 In addition, diuresis and natriuresis are typically associated with the renal vasodilation induced by these drugs when administered to hypertensive subjects. 11 Furthermore, recent studies have shown that the renal vasculature of normotensive relatives of hypertensive patients is abnormally sensitive to the dilating effect of intrarenally infused diltiazem. 12 Taking these findings into account, we studied the renal responses to an acute oral administration of the calcium entry blocking agent nifedipine in young normotensive subjects with or without one hypertensive parent.…”
Section: Prehypertensive Renal Response To Nifedipine/mon/anari Et Almentioning
confidence: 99%